Targeted consultancy services as an instrument for the development of rural SMEs - a brazilian case - Dafna Schwartz; Raphael Bar-El (European Regional Science Association (ERSA), 2002)
One of the problems that policy makers face in the process of development in many countries is the inequality between the periphery and the metropolis center. The periphery has difficulties making the structural adjustments needed to fit in the national growth, leading to growing unemployment rates, regional gaps and continuous migration to the big metropolis. One of the sectors that has a difficulty making the transition is the small business sector. Amongst the reasons is in-adequate skills and information of the business management and in some cases a lack of awareness to the importance of these fields in the potential growth to the business. In addition the government support systems for small businesses do not give an adequate response. Support programs for small businesses are mostly provided within the urban sector, and are not adapted to the needs of the rural sector. The outcome is that although there is a "potential" need among small businesses in the interior for business consultant's services and in-spite of there being a wide range system of support for small businesses at the national level, their access to such services is limited. As a consequence of the potential demand that doesn't come into expression in the existing structure and of a national supply of these services that does not meet the needs of this sector, the gaps between the rural area and the urban central area grows. Our hypothesis is that an effort to establish a link between the unexpressed demand and the inappropriate supply of services to small-scale businesses in the rural area may contribute to economic growth. We test this hypothesis by using a program that was launched in the state of Ceara, Brazil, that is set to aim at both the demand and supply, focusing on a specific population: non-agricultural businesses in the rural region. The program is intended in the first stage to create awareness in the business community to the potential for business development and to encourage their demand for such services. The program offers consultancy services suited to the special needs of businesses in the non-metropolitan region adopting a reach-out approach. The program is part of the San Jose Project directed by the Secretary of Rural Development of the State of Ceara, that is aimed to bring a reduction in poverty in rural poor areas. The first stage of the research is to identify the potential of demand for consulting services and identifying the main areas in which the consulting is needed. A questionnaire was applied to 224 entrepreneurs in three selected areas. The findings show that about all the entrepreneurs are interested in receiving the consulting services. 90% of them evaluated that they had a growth potential. The factors that they point out as main constraints are, in order: physical infrastructures (65%), marketing (60%), capital returns (52%) problems in management and labor force (37%) and administration problems (35%). The second stage of the research was focused on 140 entrepreneurs who responded to a few basic criteria and were entitled to receive basic consulting services, of up to 15 hours. At this stage the marketing turned up as a main problem, especially for businesses that are in a process of transition from local to national markets. The findings show also that the support system that provides the consultancy services needs to go through a process of adaptation. One important difficulty of the system is to switch from internal advisers to external ones who specialize in the field.
Keywords: 330